1991
DOI: 10.1073/pnas.88.5.1869
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of diabroticite rootworm beetle (Chrysomelidae) receptors for Cucurbita blossom volatiles.

Abstract: The diabroticite rootworm beetles coevolved with plants of the family Cucurbitaceae as demonstrated by their feeding dependence on the tetracyclic triterpenoid cucurbitacins. These beetles also exhibit strong attraction to phenylpropanoid volatile components of Cucurbita blossoms. A mixture of 1,2,4-trimethoxybenzene, indole, and (E)-cinnamaldehyde, all blossom components, is highly attractive to the several species of diabroticite cucumber beetles and corn rootworms and is considered a simplified Cucurbita bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 18 publications
2
26
1
Order By: Relevance
“…These results are consistent with those of an earlier study conducted in South Dakota that showed no attraction to 4-methoxyphenethanol before maize reached late dough to early dent stage, when it captured fewer D. barberi than did eugenol (Hesler et al, 1994). Both sets of results contrast with reports of high potency of 4-methoxyphenethanol in studies conducted in more easterly maize-growing regions in the U.S.A. (Metcalf & Lampman, 1991;Metcalf et al, 1995). Hesler et al (1994) hypothesized that geographical variation among populations accounts for the discrepancy and discussed other traits for which differences have been documented among geographically separated D. barberi populations.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…These results are consistent with those of an earlier study conducted in South Dakota that showed no attraction to 4-methoxyphenethanol before maize reached late dough to early dent stage, when it captured fewer D. barberi than did eugenol (Hesler et al, 1994). Both sets of results contrast with reports of high potency of 4-methoxyphenethanol in studies conducted in more easterly maize-growing regions in the U.S.A. (Metcalf & Lampman, 1991;Metcalf et al, 1995). Hesler et al (1994) hypothesized that geographical variation among populations accounts for the discrepancy and discussed other traits for which differences have been documented among geographically separated D. barberi populations.…”
Section: Discussioncontrasting
confidence: 55%
“…To my knowledge, the amine, unlike 2-phenyl-1-ethanol (Flath et al, 1978;Andersen & Metcalf, 1987), occurs in neither maize nor Cucurbitaceae, a group that probably includes ancestral hosts of diabroticite corn rootworms and has yielded many compounds affecting rootworm behaviours (Metcalf & Metcalf, 1992;Metcalf & Lampman, 1997). Metcalf & Lampman (1991) provisionally attributed attractiveness of the amine to its interaction with antennal receptors attuned to the structurally related alcohol; however, the confirmation of synergy between the amine and alcohol, at least during later maize reproductive stages, does not support this interpretation, especially when combined with results of earlier computational chemistry analyses (Petroski & Hammack, 1998).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Plants are monoecious with separate male and female flowers that last for 1 day, opening before sunrise and wilting by early afternoon (McGregor 1976). The scent of male and female Cucurbita blossoms attracts Acalymma vittatum Fabricius (striped cucumber beetle, Chrysomelidae) (Andersen and Metcalf 1986;Lewis et al 1990;Metcalf and Lampman 1991;Metcalf et al 1995;Granero et al 2004;Ferrari et al 2006), a specialist herbivore that is responsible for extensive damage to northeastern cucurbit crops (Hoffmann et al 1996). Leaves and roots of some Cucurbita species also produce volatiles that may attract cucumber beetles and other insects (Peterson et al 1994;Cosse and Baker 1999).…”
Section: Methodsmentioning
confidence: 99%